Believed-in Imaginings: The Narrative Construction of Reality.
DOI: 10.1037/10303-007
|View full text |Cite
|
Sign up to set email alerts
|

Rendering the implausible plausible: Narrative construction, suggestion, and memory.

Abstract: If we pay any attention to the media at all these days, it might be easy for some of us to conclude that we are regularly visited by aliens who abduct innocent earthlings and perform repugnant medical procedures on them and harvest their sperm and eggs, that secret satanic rituals are being conducted in the basements of our neighbors' homes, and that some of us live our lives unaware that our bodies host a boggling array of personalities.Not much more than a decade or two ago, such beliefs would be viewed as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…viii As laboratory studies have shown, what participants recall whilst hypnotized can be heavily influenced by the expectations and beliefs of the hypnotist (Lynn, Pintar, Stafford, Marmelstein & Lock, 1998;Spanos, Menary, Gabora, DuBreuil & Dewhirst, 1991, experiment 2).…”
Section: 3 4mentioning
confidence: 99%
“…viii As laboratory studies have shown, what participants recall whilst hypnotized can be heavily influenced by the expectations and beliefs of the hypnotist (Lynn, Pintar, Stafford, Marmelstein & Lock, 1998;Spanos, Menary, Gabora, DuBreuil & Dewhirst, 1991, experiment 2).…”
Section: 3 4mentioning
confidence: 99%
“…They seek the aid of a hypnotherapist to help understand their anomalous experiences, and it is during hypnotic regression sessions that they “recall” memories of having been abducted (i. e., being taken into space ships, sexually experimented on by aliens, etc.). The striking similarity of these narratives suggests a widely shared cultural script (Lynn, Pintar, Stafford, Marmelstein, & Lock, 1998). Although at least 15% of the general population has experienced sleep paralysis episodes (e. g., Hufford, 1982), not everyone concludes that alien abduction explains these anomalous experiences.…”
mentioning
confidence: 99%
“…Individuals are unlikely to develop false memories, unless they accept the suggested event as something that could plausibly have happened (Hart & Schooler, 2006;Johnson & Raye, 2000;Mazzoni & Kirsch, 2002;Pezdek, Finger, & Hodge, 1997; for a discussion of social-influence processes by which implausible ideas can come to seem plausible, see Lynn, Pintar, Stafford, Marmelstein, & Lock, 1998). To the extent that it is persuasive, false evidence, by definition, increases the perceived plausibility of the suggested event.…”
mentioning
confidence: 99%